Long-term outcome of patients with cardiolaminopathy undergoing defibrillator implantation: single-center experience. (14th October 2021) - Dusi, V; Masiello, L.C; Vicentini, A; Savastano, S; Petracci, B; Sanzo, A; Baldi, E; Greco, A; Turco, A; Raineri, C; Scelsi, L; Ghio, S; et al.
Abstract: Background: Mutations in the LMNA gene are associated with a high arrhythmic risk. The history of the disease in patients undergoing ICD implantation is poorly characterized. Purpose: To evaluate the phenotype of patients with cardiolaminopathy at the time of first ICD implantation, the incidence, characteristics and timing of ventricular arrhythmias (VAs) during follow up and the predictive value of the European score (that assigns a point each to non-sustained VT (NSVT), left ventricular ejection fraction (LVEF)<45% at first contact, male sex and non-missense mutations) and of the Wahbi score (that also includes conduction disturbances) for both VAs and heart failure (HF) related outcomes. Methods: Patients were identified retrospectively. Clinical and device data were collected at baseline and during follow-up. Results: We identified 26 patients (54% male, 42±8 years, 31% with familial history of sudden cardiac death, 31% with non-missense mutation) undergoing ICD implantation, 96% in primary prevention, 47% with single chamber ICD, 38% with dual chamber ICD. At the time of implantation, 30% had skeletal muscle involvement, 15% history of syncope, 4% of cardiac arrest, 62% previous NSVT. Also, 38% had a history of supraventricular arrhythmias and 61% had AV conduction disturbances. LVEF was 41±11%, 35% were in NYHA class ≥2, the mean European and Wahbi scores were 2.1±0.8 and 18.2±8.9, respectively. During 8.3±5 years, 15% were transplanted, 8% died due to HF, 4% underwent LVAD implantation, despite 31% having received an upgrade to CRT-D. Appropriate device interventions occurred in 46% of patients with a median time to first event of 29 months (IQR 13–93), for a total of 137 ATP, 51% of which effective (median 3ATP/patient, IQR 1–8) and of 26 shocks, 96% of which effective (median 2 shocks/patient, IQR 1–3); 12% had an arrhythmic storm. The first treated arrhythmia was a polymorphic VT/VF in 17%, a monomorphic VT in the others (medium cycle length 293±37 msec). Survival free from appropriate ICD interventions at 1 and at 5 years was 75% and 19% respectively in case of a European score ≥3 vs 94% and 82% in case of a score <3 (Logrank test p<0.01), 72% and 46% in case of Wahbi score ≥30 vs 100% and 86% with score <30 (p<0.01), with no differences in terms of death/transplant (figure). At last follow-up, 92% of patients a were taking beta-blocker, 42% amiodarone, 8% sotalol, 4% flecainide, 8% mexiletine. Also, 4% had undergone invasive VT ablation, 8% bilateral cardiac sympathetic denervation. Conclusions: Patients with cardiolaminopathy are at a high risk of both arrhythmic and heart failure progression over the first decade after implantation of the first ICD. A European score ≥3 identifies patients with 5-year shock/ATP free survival of less than 20% but does not predict death/transplantation. The first arrhythmic event in these patients is more frequently a rapid monomorphic VT with modest ATP efficacy. Funding Acknowledgement: Type of funding sources: None.